The Influence of Travel Literature between Korea and the West - Alexandra Bîja (Linguaculture)
This article explores the reciprocal influences of travel literature between Korea and the West from the late 19th to the mid-20th century, a transformative period marked by Korea’s opening to global exchange and its subsequent colonization. It investigates how Korean envoys, reformers, and intellectuals used their travel experiences in the United States and Europe to articulate visions for national modernization, gender reform, and cultural renewal. Their writings functioned as blueprints for Enlightenment-inspired reform and laid intellectual groundwork for movements like the Independence Club and the New Woman movement. In parallel, the travel narratives of Western visitors to Korea shaped Western public opinion and diplomatic postures toward the Korean peninsula. These narratives often oscillated between admiration for Korean traditions and orientalist assumptions about cultural stagnation, and in the colonial period, increasingly echoed or resisted Japanese imperial propaganda. This article examines how travel literature served as a vehicle for intercultural exchange, the transmission of ideologies, and the reimagining of national identities.